Endophytic Microbiome Is a Unique Repository of Bio-Foes Against Toxigenic Fungi Harming Peanut Productivity - Nagwa I. M. Helal; Mona H. Badawi; Abeer M. El-Hadidy; Mohamed K. M. Agha; Ahmed Abou-Shady; Mohamed Fayez (Microbiology Research, 2025)
The major objective was to investigate the protective capabilities of endophytic bacterial strains isolated from a number of medicinal plant species towards Aspergillus spp. secured from the internal tissues of fungi-infected peanuts. Among 32 fungal isolates surveyed for mycotoxin production in various culture media (PDA, RBCA, YES, CA), 10 isolates qualitatively producing AFB1, besides 10 OTA-producers, were assayed by HPLC for quantitative toxin production. Aspergillus spp. isolate Be 13 produced an extraordinary quantity of 1859.18 μg mL−1 AFB1, against the lowest toxin level of 280.40 μg mL−1 produced by the fungus isolate IS 4. The estimated amounts of OTA were considerably lower and fell in the range 0.88–6.00 μg mL−1; isolate Sa 1 was superior, while isolate Be 7 seemed inferior. Based on ITS gene sequencing, the highly toxigenic Aspergillus spp. isolates Be 13 and Sa 1 matched the description of A. novoparasiticus and A. ochraceus, respectively, ochraceus, respectively, which are present in GenBank with identity exceeding 99%. According to 16S rRNA gene sequencing, these antagonists labeled Ar6, Ma27 and So34 showed the typical characteristics of Pseudomonas aeruginosa, Bacillus subtilis and Bacillus velezensis, respectively, with similarity percentages of 99–100. The plant growth-promoting activity measurements of the identified endophytes indicated the production of 16.96–80.00 μg/100 mL culture medium of IAA. Phosphate-solubilizing capacity varied among endophytes from 2.50 to 21.38 μg/100 mL. The polysaccharide production pool of bacterial strains ranged between 2.74 and 6.57 mg mL−1. P. aeruginosa Ar6 and B. velezensis successfully produced HCN, but B. subtilis failed. The in vitro mycotoxin biodegradation potential of tested bacterial endophytes indicated the superiority of B. velezensis in degrading both mycotoxins (AFB1-OTA) with average percentage of 88.7; B. subtilis ranked thereafter (85.6%). The 30-day old peanut (cv. Giza 6) seedlings grown in gnotobiotic system severely injured due to infection with AFB1/OTA-producing fungi, an effect expressed in significant reductions in shoot and root growth traits. Simultaneous treatment with the endophytic antagonists greatly diminished the harmful impact of the pathogens; B. velezensis was the pioneer, not P. aeruginosa Ar6. In conclusion, these findings proved that several endophytic bacterial species have the potential as alternative tools to chemical fungicides for protecting agricultural commodities against mycotoxin-producing fungi.